Single-Item and Associative Working Memory in Stroke Patients - Bonnie van Geldorp; Roy P. C. Kessels; Marc P. H. Hendriks (Behavioural Neurology)
In this study, we examined working memory performance of stroke patients. A previous study assessing amnesia patients found deficits on an associative working memory task, although standard neuropsychological working memory tests did not detect any deficits. We now examine whether this may be the case for stoke patients as well. The current task contained three conditions: one spatial condition, one object condition and one binding condition in which both object and location had to be remembered. In addition, subsequent long-term memory was assessed. The results indicate that our sample of stroke patients shows a working memory deficit, but only on the single-feature conditions. The binding condition was more difficult than both single-feature conditions, but patients performed equally well as compared to matched healthy controls. No deficits were found on the subsequent long-term memory task. These results suggest that associative working memory may be mediated by structures of the medial temporal lobe.